(untitled) (LEARNing Landscapes, 2022)
Creating climates that embrace justice, equity, diversity, and inclusion, must involve learning by everyone in the community. Although active learning techniques for promoting cognitive learning have received much attention in recent decades, techniques for affective learning are less developed. Affective learning is, however, essential to this particular area of change. Using the example of an innovative workshop about creating more welcoming environments for Disabled people, this article demonstrates how Research-Based Theatre, in combination with other active learning techniques, can promote affective learning and encourages readers to reflect on how they might incorporate creative, arts-based, research-informed approaches.